Systems thinking for sustainable crime prevention: planning for risky places - Ceccato, Vania (Routledge, Taylor&Francis Group, 2025)
"This book offers a comprehensive overview of areas with elevated levels of crime (risky places). With examples from the US, the UK, Sweden, Nigeria, Brazil, China, Australia, the book shows what can be learned from risky places, and identifies ways to address their inherent problems"--